From ponds to prosperity: Empowering Kalukku Barat Village through participatory resource mapping and aquaculture product development - Deril, Virda Evi Yanti; Mahful, Rafid; Sintia, Windy Septi; Syamsiar, Nur Ratika; Lestari, Sri Apriani Puji; Astinawaty, Astinawaty; Saputra, Ade Guna; Zani, Nanda Mutiara (Universitas Muhammadiyah Magelang, 2025)
The community engagement team collaborated with the Village Government of Kalukku Barat to optimize the management of the village's potential in the leading fishery sector, aiming for village self-reliance. Generally, this activity was conducted to maximize community participation in accelerating independent and sustainable village development by leveraging local potential and characteristics. The activities included assisting in the participatory mapping of natural resource potential and providing training in developing value-added processed aquaculture products. The outputs of the activity include a map showing the distribution of natural resource potential and the formation of a community business group focused on processing pond fishery products, namely fish floss (abon ikan) and milkfish crackers (ampang bandeng). The results of this activity also provide a clear picture to the local community, as owners and/or managers of the land, regarding how to manage their potential resources to enhance the economy independently and sustainably.